Multimodal emotion perception after anterior temporal lobectomy (ATL) - Milesi, Valérie; Cekic, Sezen; Péron, Julie; Frühholz, Sascha; Cristinzio, Chiara; Seeck, Margitta; Grandjean, Didier (Frontiers in Human Neuroscience, 2014)
In the context of emotion information processing, several studies have demonstrated the involvement of the amygdala in emotion perception, for unimodal and multimodal stimuli. However, it seems that not only the amygdala, but several regions around it, may also play a major role in multimodal emotional integration. In order to investigate the contribution of these regions to multimodal emotion perception, five patients who had undergone unilateral anterior temporal lobe resection were exposed to both unimodal (vocal or visual) and audiovisual emotional and neutral stimuli. In a classic paradigm, participants were asked to rate the emotional intensity of angry, fearful, joyful, and neutral stimuli on visual analog scales. Compared with matched controls, patients exhibited impaired categorization of joyful expressions, whether the stimuli were auditory, visual, or audiovisual. Patients confused joyful faces with neutral faces, and joyful prosody with surprise. In the case of fear, unlike matched controls, patients provided lower intensity ratings for visual stimuli than for vocal and audiovisual ones. Fearful faces were frequently confused with surprised ones. When we controlled for lesion size, we no longer observed any overall difference between patients and controls in their ratings of emotional intensity on the target scales. Lesion size had the greatest effect on intensity perceptions and accuracy in the visual modality, irrespective of the type of emotion. These new findings suggest that a damaged amygdala, or a disrupted bundle between the amygdala and the ventral part of the occipital lobe, has a greater impact on emotion perception in the visual modality than it does in either the vocal or audiovisual one. We can surmise that patients are able to use the auditory information contained in multimodal stimuli to compensate for difficulty processing visually conveyed emotion.